Design of a New Telescope Control System for Use in Astronomical Transient Events - Selcuk Helhel; Murat Dindar; Ekrem Kandemir; Saniye Dindar; Tuncay Ozisik (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Robotic autonomous telescopes provide highlevel control by selecting astronomical targets for observation, and they usually run under the control of a scheduler. TalonVIEW is a newly designed robotic autonomous telescope control system (TCS) for 16 inches telescope mount for use in astronomical transient events. The telescope control algorithm was implemented in PXI chassis written in GProgramming (LabVIEW) on realtime operating system(PharLab) from scratch. A new TCP/IP library was also implemented in Talon software to communicate with Pharlab in PXI chassis. Initial setup without any permanent pier and polar alignment showed that the pointing error of the telescope has been obtained as 2.22 arcminutes (132 arcseconds) in RA axis (horizontal axis of the image) and 25 arcseconds in Dec axis (vertical axis of the image), and tracking error has been observed as 4.8 arcseconds per second.